Mapping differential cellular protein response of mouse alveolar epithelial cells to multi-walled carbon nanotubes as a function of atomic layer deposition coating. Issue 3 (16th March 2017) - Hilton, Gina M.; Taylor, Alexia J.; Hussain, Salik; Dandley, Erinn C.; Griffith, Emily H.; Garantziotis, Stavros; Parsons, Gregory N.; Bonner, James C.; Bereman, Michael S.
Abstract: Carbon nanotubes (CNTs), a prototypical engineered nanomaterial, have been increasingly manufactured for a variety of novel applications over the past two decades. However, since CNTs possess fiber-like shape and cause pulmonary fibrosis in rodents, there is concern that mass production of CNTs will lead to occupational exposure and associated pulmonary diseases. The aim of this study was to use contemporary proteomics to investigate the mechanisms of cellular response in E10 mouse alveolar epithelial cells in vitro after exposure to multi-walled CNTs (MWCNTs) that were functionalized by atomic layer deposition (ALD). ALD is a method used to generate highly uniform and conformal nanoscale thin-film coatings of metals to enhance novel conductive properties of CNTs. We hypothesized that specific types of metal oxide coatings applied to the surface of MWCNTs by ALD would determine distinct proteomic profiles in mouse alveolar epithelial cells in vitro that could be used to predict oxidative stress and pulmonary inflammation. Uncoated (U)-MWCNTs were functionalized by ALD with zinc oxide (ZnO) to yield Z-MWCNTs or aluminum oxide (Al2 O3 ) to yield A-MWCNTs. Significant differential protein expression was found in the following critical pathways: mTOR/eIF4/p70S6K signaling and Nrf-2 mediated oxidative stress response increased following exposure to Z-MWCNTs, interleukin-1 signaling increased following U-MWCNT exposure, and inhibition of angiogenesis by thrombospondin-1, oxidative phosphorylation, and mitochondrial dysfunction increased following A-MWCNT exposure. This study demonstrates that specific types of metal oxide thin film coatings applied by ALD produce distinct cellular and biochemical responses related to lung inflammation and fibrosis compared to uncoated MWCNT exposure in vitro .